FAMILY’ CONCEPT, CHARACTERS AND FUNCTIONS - Laura, Viculescu Cetean (Anales Universitatis Apulensis Series Jurisprudentia; No 16 (2013): ANNALES UNIVERSITATIS APULENSIS - SERIES JURIPRDENTIA, 2013)
Family is the most important core social and legal regulation shall be subject to the favorite research of family law doctrine. In this paper we propose to analyze the family concept, characters and functions. Keywords: family, functions, characters, concept, rights and obligations